2014
DOI: 10.1038/eye.2014.253
|View full text |Cite
|
Sign up to set email alerts
|

Larger and near-term baby retinopathy: a rare case series

Abstract: Purpose To report retinopathy in a series of four babies unusually beyond the screening standards reported so far in the literature. Methods During routine screening for retinopathy of prematurity, we detected retinopathy in four babies who were surprisingly bigger and older than the screening standards. The gestational age (GA), birth weight (BW), post menstrual age at first examination and significant perinatal events were noted. The retinopathy details imaged by the RetCam were classified as per ICROP revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…This was nearly similar to our previous report on term and near term baby retinopathy. 11 The cystic fovea seen in these babies has not been reported by any of the 3 other newborn screening studies analyzed in this report though, some other studies have reported similar transient macular cysts documented in SDOCT in healthy infants. [12][13][14] In fact, we have seen similar finding in 6 babies screened for ROP under a separate project (unpublished data).…”
Section: Resultssupporting
confidence: 49%
“…This was nearly similar to our previous report on term and near term baby retinopathy. 11 The cystic fovea seen in these babies has not been reported by any of the 3 other newborn screening studies analyzed in this report though, some other studies have reported similar transient macular cysts documented in SDOCT in healthy infants. [12][13][14] In fact, we have seen similar finding in 6 babies screened for ROP under a separate project (unpublished data).…”
Section: Resultssupporting
confidence: 49%
“…Retinal vascular changes similar to ROP in healthy full/nearterm infants with a normal birth weight were sporadically reported in previous studies (5,7). And among them, most of infants were with supplementary oxygen exposure.…”
Section: Discussionmentioning
confidence: 71%
“…In full term infants, retinopathies can occur with clinical features that can appear similar to ROP (4)(5)(6). ROP-like retinopathies (ROPLR) refers to ROP developing in full/near-term neonates at a birth weight heavier than 2400 g (7). Some potential risk factors, such as brain anomalies and defects and poor maternal nutrition, increased oxygen tension in the retina after birth, hypoxic-ischemic encephalopathy (HIE) and family exudative vitreoretinopathy (FEVR) were suspected to be related to the occurrence of ROPLR (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The infant in our case had a GA of 35 weeks and BW of 1700 g. Studies from several parts of the world have reported that larger premature infants who received improper oxygen therapy can develop ROP [ 11 , 12 ]. Our case has already been diagnosed with TOF at birth and required supplemental oxygen administration due to systemic hypoxia.…”
Section: Discussionmentioning
confidence: 87%
“…A reason for the development of retinal vascular abnormalities in TOF has been suggested to be ischemia. In general, oxygen saturation of the arterial blood cannot be maintained in infants with a CCHD; therefore an ischemic environment of the body arises [ 11 ]. The role of hypoxia has been demonstrated to be associated with nonperfused peripheral retina in animal models [ 14 ].…”
Section: Discussionmentioning
confidence: 99%